DEVELOPMENT OF SYSTEMS FOR EFFECTIVE ESTIMATION OF CREDIT SCORES - Aitim , A.; Sembina, G. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The article represented that in connection with the increasing importance of the time factor, automated methods of assessing creditworthiness are now becoming increasingly important. With mass consumer lending, practically in the presence of a potential borrower, it becomes necessary to decide on granting a loan. To operate profitably in the retail lending market, an effective risk assessment system is required, which would make it possible to cut off unreliable borrowers in advance and not refuse reliable borrowers, and reasonably determine the size of a consumer loan or a credit card limit. This system should create a margin of safety for the bank. One of such automated methods for assessing the creditworthiness of a counterparty is the scoring method.